Insecticidal activity of alkaloids from Macleaya microcarpa against several species of insect pests - FENG Gang; ZHANG Jing; LI Xiu-wei; FENG Jun-tao; ZHANG Xing (浙江大学学报. 农业与生命科学版)
To verify the bioactive spectra and action of alkaloids from Macleaya microcarpa, the insecticidal activities of the alkaloids were investigated in the laboratory against the third instar larvae of Mythimna separata, fifth instar larvae of Pieris rapae, third instar larvae of Plutella xylostella, third instar larvae of Helicoverpa armigera, and adults of Myzus persicae and Schizaphis graminum. The results indicate that the alkaloids from M. microcarpa demonstrated the stomach poison and antifeedant activities against the larvae of M. separata, P. rapae and P. xylostella with the AFC50 values of antifeedant (48 h) and LC50 values of stomach poison (96 h) of 0.265, 0.557, 0.543 g·L-1 and 0.106, 0.123, 0.166 g·L-1, respectively. The alkaloids also showed strong contact activity against M. persicae and S. graminum, and the LC50 values (48 h) were 0.362 and 0.710 g·L-1, respectively. The growth inhibition percentage against third instar larvae of H. armigera treated with the alkaloids (5 g·L-1) was about 69.5% (7 d). Morever, egg hatch and larval survival of M. separata were only 58.8% and 22.6%, respectively, at the day 5 after treatment with the alkaloids at a concentration of 2.5 g·L-1, which were significantly lower than those of control and other treatments.